Immunogenicity and safety of an Entamoeba histolytica adjuvanted protein vaccine candidate (LecA+GLA-3M-052 liposomes) in rhesus macaques - Mayuresh M. Abhyankar; Feifan Xu; Deborah Chavez; Anna Goodroe; Elda Mendoza; Christopher Chen; Dhiraj K. Singh; Fernando Varnador; Sandra J. Sivananthan; Robert Kinsey; William R. Lykins; Brynn M. Murphy; et al. (Taylor & Francis Group, 2024)
Entamoeba histolytica, the causative agent of amebiasis, is one of the top three parasitic causes of mortality worldwide. However, no vaccine exists against amebiasis. Using a lead candidate vaccine containing the LecA fragment of Gal-lectin and GLA-3M-052 liposome adjuvant, we immunized rhesus macaques via intranasal or intramuscular routes. The vaccine elicited high-avidity functional humoral responses as seen by the inhibition of amebic attachment to mammalian target cells by plasma and stool antibodies. Importantly, antigen-specific IFN-γ-secreting peripheral blood mononuclear cells (PBMCs) and IgG/IgA memory B cells (BMEM) were detected in immunized animals. Furthermore, antigen-specific antibody and cellular responses were maintained for at least 8 months after the final immunization as observed by robust LecA-specific BMEM as well as IFN-γ+ PBMC responses. Overall, both intranasal and intramuscular immunizations elicited a durable and functional response in systemic and mucosal compartments, which supports advancing the LecA+GLA-3M-052 liposome vaccine candidate to clinical testing.